Analysis of the History of Governmental Changes from Amir To the Caliph During Abdurrahman III in Andalusia (929 AD) - Ibnu Rusydi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This paper aims to analyze the history of the change of government from the Amir to the Caliph during Abdurrahman III in Andalusia (929 AD). The method used in this research is historical research. The historical method here is the process of critically examining and analyzing past records and relics. This study concludes that the reason for Abdurrahman III proclaiming himself as a caliph with the title of Caliph al-Nashir Linillah in 929 AD was to counter the influence of the Caliphate of the Fatimid dynasty which was Shiite and restore the authority of the Sunnis due to the weakness of the Abbasid dynasty in Baghdad. With the emergence of Abdurrahman III as head of government with the title of caliph, the Islamic world has three caliphs in an unprecedented period. Abdurrahman III became the first person to assume the title of Amir al-Mu'minin in Andalusia. This title was used by the rulers after until the end of the reign of the Umayyads in Andalusia.